Analyzing the Mathematical Models behind the Collective Intelligence of Bees - B, Selva Rani; S, Vairamuthu (IJRDO -Journal of Computer Science Engineering, 2015)
For any system, a mathematical model is a generalization and representation of its features in a very precise manner. In this paper, we carried out a survey on mathematical models behind the bees. The term collective intelligence, popularly known as swarm intelligence studies the cooperative behavior among the natural species. This self-organized; de-centralized intelligence and cooperation among individuals of a group like ants, bacteria, bees, birds, fishes, termites, wolves, pelicans etc. help them to achieve a common goal like foraging, defending, constructing nests and so on. They frame and follow very simple rules in their entire life cycle, communicate locally in an efficient manner, assist each other in all the situations and many scientific and engineering problems have been solved inspired by these characteristics of swarms.